The hard sell of paradise : Hawai'i, Hollywood, tourism - Sperb, Jason, 1978- (State University of New York Press, 2022)
"Traces the complex and contradictory representations of Hawai'i in popular film and television programs from the 1930s to the 1970s"-- Provided by publisher.
Keywords: Hawaii -- On television.; Motion pictures -- United States -- History -- 20th century.; Television programs -- United States -- History -- 20th century.; Hawaii -- In motion pictures.; Hawaii -- In popular culture.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; Émissions télévisées -- États-Unis -- Histoire -- 20e siècle.; Hawaii -- Dans la culture populaire.; Hawaii -- À la télévision.; PERFORMING ARTS / Film & Video / History & Criticism.; Motion pictures; Television programs; Hawaii; United States; 1900-1999; History